Pengenaan Pajak Penghasilan di Indonesia (Pasal 21 Undang-Undang Nomor 36 Tahun 2008 Tentang Pajak Penghasilan) - Gede Sastrawan; Ida Ayu Putu Indah Wahyoni (Universitas Pendidikan Ganesha, 2021)
Every county has the same goal, namely to create the wlfare of its people. Especially in Indonesia, which is a rule of law based on Pancasila and the 1945 Constitution. The issue stated in the preamble to the 1945 Constitution states the general welfare on the basis of social justice. Then besides that there is the aim of the state which is the common interest of all the people, so that the costs that msu be incurred to realize state programs are also shared responsibility. To cover state expenditures in order to realize its programs, the state seeks financing by collecting taxes. One of them is from the imposition of income tax. Income tax is regulated in Law Numbers 36 Years 2008. One of the types of distribution is Income Tax Article 21 (PPh 21), which regulates taxes on income in the form of salaries, wages, allowances, and other payments that are obtained by individual tacpayers. Domestic individuala in connection with work or position of services and activities.